1994
DOI: 10.1107/s0907444994001988
|View full text |Cite
|
Sign up to set email alerts
|

Observation of growth steps, spiral dislocations and molecular packing on the surface of lysozyme crystals with the atomic force microscope

Abstract: The (110) faces of lysozyme crystals in their mother liquor have been investigated using an atomic force microscope (AFM) in height mode. Crystal growth and dissolution steps, as well as simultaneous growth and dissolution in pits, have been observed. Screw dislocations were also observed but the fine structure has not yet been investigated. Images that may possess molecular resolution were obtained and compared with theoretical images based on the crystallographic structure and the effects of arbitrary tip pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
65
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(70 citation statements)
references
References 0 publications
5
65
0
Order By: Relevance
“…The step height presumably corresponds to the unimolecular growth layers observed on this face (Durbin & Feher, 1990;Durbin & Carlson, 1992). Unfortunately, Durbin and coworkers do not report growth step heights as were reported for the (110) face by Konnert et al (1994). Nevertheless, 34.2 A Ê is much closer than 17.1 A Ê to the 28.0 Â 28.0 Â 37.9 A Ê dimensions of single lysozyme molecules as shown in Fig.…”
Section: Growth Mechanism and Surface Morphologymentioning
confidence: 72%
See 4 more Smart Citations
“…The step height presumably corresponds to the unimolecular growth layers observed on this face (Durbin & Feher, 1990;Durbin & Carlson, 1992). Unfortunately, Durbin and coworkers do not report growth step heights as were reported for the (110) face by Konnert et al (1994). Nevertheless, 34.2 A Ê is much closer than 17.1 A Ê to the 28.0 Â 28.0 Â 37.9 A Ê dimensions of single lysozyme molecules as shown in Fig.…”
Section: Growth Mechanism and Surface Morphologymentioning
confidence: 72%
“…It was also shown that the 4 3 helix is formed by strong bonds and that crystal growth is likely to proceed in a manner which preserves this unit's structure. These predictions were con®rmed by AFM scans which showed that the (110) faces are formed by planes corresponding to this construction (Konnert et al, 1994;Li, Perozzo et al, 1999). Further con®rmation was provided by a recent study of the crystal-packing arrangement employing a somewhat different approach (Strom & Bennema, 1997a,b).…”
Section: Growth Mechanism and Surface Morphologymentioning
confidence: 82%
See 3 more Smart Citations